Women directors and firm performance: Malaysian evidence post policy announcement - Ahmad, Maslina; Raja Kamaruzaman, Raja Nur Syazwani; Hamdan, Hamdino; Annuar, Hairul Azlan (Emerald Insight, 2019)
In 2011, the Malaysian cabinet approved the policy that all board of directors of companies listed on the Bursa Malaysia should consist of 30 per cent women in decision-making positions by the year 2016. The purpose of this paper is to examine the association between the presence of women on the board and firms’ performance following the introduction of the diversity policy. The analysis uses the information of the top 200 Malaysian public listed companies for the financial year 2011–2013. The multiple regression analysis is used to estimate the relationship between the firm performance (return on assets (ROA)) as the dependent variable and the independent variables.The results show that during the period under study, the proportion of women directors on board is negatively correlated with ROA. This indicates that the firm performance may not be dependent on the number of women directors on board. However, the results of the study also show that the academic backgrounds of the women board members add some value toward generating better firm performance. The findings encourage public listed companies to appoint women with the necessary qualities as members of the board and not to simply increase the number of women on boards.